The effect of digital leadership in creating smart organizations in the Jordanian private universities - Momani, Khaled; badarneh, Atia Mohd Al; Shishakly, Rima; Hamadneh, Burhan Mahmoud; Almaiah, Mohammed Amin (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to define the effect of digital leadership in creating smart organizations in Jordanian private universities. A convenient random sample consisting of 283 faculty members was selected and asked to respond to a questionnaire. The results of the study showed that there is a positive effect of total digital leadership on total smart organizations in Jordanian private universities. In light of the results, recommendations were provided, the most important being that Jordanian private universities should develop procedures encouraging administrative and academic leaders to make technology an integral part of their work when interacting with employees.